Co-carcinogenesis: Human Papillomaviruses, Coal Tar Derivatives, and Squamous Cell Cervical Cancer - Haverkos, Harry W.; Haverkos, Gregory P.; O’Mara, Michael (Frontiers in Microbiology, 2017)
Cervical cancer (CC) is the fourth most common cancer among women worldwide. Human papillomaviruses (HPV) play a major role in the etiology of CC, with several lines of epidemiologic and experimental evidence supporting a role for non-viral (co-carcinogens) and host genetic factors in controlling the risk for progression to neoplasia among HPV-infected individuals. The role of co-carcinogens in the development of CC is significant in the developing world where poor sanitation and other socio-economic conditions increase the infectious cancer burden. Here, we discuss how exposure to environmental factors such as coal tar products from cigarette smoking, tar-based sanitary products, and inhaled smoke from biomass-burning stoves, could activate host pathways involved in development of HPV-associated squamous cell cancers in resource-limited settings. Understanding interactions between these pathways with certain oncogenic HPV genotypes may guide implementation of strategies for control and treatment of HPV-associated cancers that develop in populations at high risk of exposure to various co-carcinogens.